2020
DOI: 10.3390/ijms21103709
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Disorder in Tetratricopeptide Repeat Proteins

Abstract: Among the realm of repeat containing proteins that commonly serve as “scaffolds” promoting protein-protein interactions, there is a family of proteins containing between 2 and 20 tetratricopeptide repeats (TPRs), which are functional motifs consisting of 34 amino acids. The most distinguishing feature of TPR domains is their ability to stack continuously one upon the other, with these stacked repeats being able to affect interaction with binding partners either sequentially or in combination. It is known that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 149 publications
(243 reference statements)
1
3
0
Order By: Relevance
“…This PPI network with an average node degree of 13.8, average local clustering coefficient of 0.871, expected number of edges of 49, and PPI enrichment p -value of <10 –16 includes 34 proteins/genes connected by 235 interactions. The presence of high levels of functional disorder in human RGPD4 is in line with the results of our global analysis of a set of human TPR proteins, where it was shown that these TPR proteins contain different levels of intrinsic disorder and possess functional IDPRs that are utilized in the PPIs and often serve as targets of various PTMs.…”
Section: Resultssupporting
confidence: 86%
“…This PPI network with an average node degree of 13.8, average local clustering coefficient of 0.871, expected number of edges of 49, and PPI enrichment p -value of <10 –16 includes 34 proteins/genes connected by 235 interactions. The presence of high levels of functional disorder in human RGPD4 is in line with the results of our global analysis of a set of human TPR proteins, where it was shown that these TPR proteins contain different levels of intrinsic disorder and possess functional IDPRs that are utilized in the PPIs and often serve as targets of various PTMs.…”
Section: Resultssupporting
confidence: 86%
“…However, with a few exceptions, 32,33 these servers are not designed with genome‐scale structural bioinformatics or comparative genomics/proteomics in mind. We previously developed a web‐crawler style disorder predictor for internal usage that was implemented into a tool we refer to as Disorder Spider (DiSpi) in our previous studies, see for example, refs 34–39 . DiSpi works by first aggregating disorder profiles from six well‐known disorder predictors: PONDR VLXT, 40 PONDR VL3, 41 PONDR VLS2B, 42 PONDR‐FIT, 43 IUPred‐Short, and IUPred‐Long 44 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed a web-crawler style disorder predictor for internal usage that was implemented into a tool we refer to as Disorder Spider (DiSpi) in our previous studies, see for example, refs. [34][35][36][37][38][39] DiSpi works by first aggregating disorder profiles from six well-known disorder predictors: PONDR VLXT, 40 PONDR VL3, 41 PONDR VLS2B, 42 PONDR-FIT, 43 IUPred-Short, and IUPred-Long. 44 Then, a mean disorder profile (MDP) is computed along with the standard error.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted percent of intrinsically disordered residues (PPIDR) is defined as the number of disordered residues divided by the length of the sequence. Based on their levels of intrinsic disorder, proteins are classified as highly disordered (MDS ≥ 0.5, PPIDR ≥ 30%), moderately disordered (0.25 ≤ MDS < 0.5, 10% ≤ PPIDR < 30%) and ordered (MDS < 0.25, PPIDR < 10%) [93]. The MDS is not directly related to PPIDR (in particular, at 100% PPIDR value of MDS can be anything in the range from 0.5 to 1); therefore, these two methods of protein intrinsic disorder evaluation should be analyzed using correlation.…”
Section: Disorder Prediction: Description and Comparison Of Algorithmsmentioning
confidence: 99%